Analisis Sentimen Berbasis Aspek Program Koperasi Desa Merah Putih Menggunakan IndoBERT - gea, yuris mardayani; Berutu, Sunneng Sandino; Jatmika, Jatmika (Program Studi Teknik Informatika Universitas Multi Data Palembang, 2026)
The Koperasi Desa Merah Putih program is a strategic initiative requiring evaluation through public perception monitoring. This study employs Aspect-Based Sentiment Analysis (ABSA) using the IndoBERT transformer model via a two-stage approach: aspect-opinion extraction using BIO labeling (Token Classification) and sentiment polarity determination (Sequence Classification). A dataset of 12,013 entries from Platform X underwent systematic preprocessing and was trained using an 80:20 stratified split to ensure label balance. Model performance, evaluated through accuracy, precision, recall, and F1-score, demonstrated high reliability with 79% accuracy. Collectively, the analysis identified 4,917 neutral, 3,961 negative, and 3,135 positive opinions. Specifically, the